A Bourdieuan Analysis of Qualitative Authorship in Entrepreneurship Scholarship. (15th August 2014) - Drakopoulou‐Dodd, Sarah; McDonald, Seonaidh; McElwee, Gerard; Smith, Robert; Karatas‐Ozkan, Mine; Anderson, Alistair R.; Fayolle, Alain; Howells, Jeremy; Condor, Roland
<x xml:space="preserve">Abstract</x> Empirically, this study builds on responses from leading qualitative entrepreneurship scholars. We carry out a Bourdieuan analysis of the field of entrepreneurship scholarship—particularly heterodox qualitative writing—and the way that scholars learn to play this game (habitus). It discusses unchallenged assumptions (doxa), commitment to shared stakes (illusio), the practice to achieve these stakes (practice), and the struggle for glories and riches (capital). By deploying Bourdieu's frame, we have been able to expose key processes, structures, and relationships within qualitative entrepreneurship authorship. These offer four types of practical outcomes: guidance for good practice; insights into emotional aspects of authorship; warnings of potentially dysfunctional practices; and a celebration of our successes.